Providing Pastoral Care Services in a Clinical Setting to Veterans At-Risk of Suicide - Kopacz, Marek S. (Journal of religion and health, 2013)
The value of enhanced spiritual wellbeing has largely been overlooked as part of suicide prevention efforts in Veterans. The aim of this qualitative study is to examine the clinical pastoral care services provided by VA Chaplains to Veterans at-risk of suicide. This study was conducted using in-depth interviews with five Chaplains affiliated with a medical center located in upstate New York. This study was able to show that some at-risk individuals do actively seek out pastoral care, demonstrating a demand for such services. In conclusion, a pastoral care framework may already exist in some clinical settings, giving at-risk Veterans the opportunity to access spiritual care.